Teachers' Beliefs Regarding Language Learner Autonomy and Practices of Project-Based Education: A Case Study of An Indonesian EFL Teacher (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
Language learner autonomy can be defined as learning outside the classroom in which learners direct their own learning independently of teachers.One of the approaches supports learner autonomy is the project-based education. The project that the Indonesian EFL teacher (the participant of this study) assigned to her English class was an English drama performance. In the end of the course, her students had to perform the play. This project required active engagement of students' efforts over an extended period of time. This paper reveals the beliefs of the EFL teacher about learner autonomy. In addition, this study investigates the practices that the teacher used in enhancing autonomy. The findings are based on an analysis and interpretation of the data gathered from questionnaires and interviews. The results reveal the teacher's beliefs and suggest that preparing activities that promote language learner autonomy is essential for English teachers.